Selection of corrosion-resistant alloy tubulars for offshore applications - Schillmoller, C. M. (Nickel Development Institute, 1989)
The role of corrosion resistant alloys for deep gas wells has become well established. Traditionally, corrosion resisting alloys are used in oil and gas production as a last resort when protective coatings, cathodic protection or corrosion inhibitors prove to be inadequate. In this booklet, guidelines in alloy selection and a number of case histories is presented to assist the design engineer.
Keywords: Corrosion resistant alloys.; Offshore structures -- Corrosion.; elektronické knihy; electronic books